We who produce pearls - Ho, Joanna (Orchard Books, an imprint of Scholastic Inc., 2024)
"An anthem for Asian America that celebrates the richness and diversity within the Asian American identity and serves as a reminder of our self worth, our legacy and most of all, our destiny. "--Provided by publisher.